(3GdJbQjH aj Ydhe GdMOjKs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3YKeGf Hf YHO GdQMef (B((3UdGM GdOjf(B) (3GHf YKeGf Hf ehSi Hf CHj GdfUQ GdfUQj GdTgQRhQj GdcQOj GdTQNGfj, CHh YeQh, Jbj GdOjf, GdeYQha HGHf GdUdGM,J (B643 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf Yde GdMOjK ef GaVd GdbQH hGdPi GNJUQJg ef cJGH GHf GdUdGM QVi Gddg Yfg GHGdZ ajg ai GdGNJUGQ ef ZjQ GNdGd HGdebUhO GdMOjK UMjM hMSf hVYja s
(3BNQgG (B:s
(3ef cGf fGbdI ef HdO Edi HdO hGQGO GdGfJSGH GdjgeG adjHOC HGdChd afbhd ai fGbdI bGd CHh YHO Gddg Hf GdeHGQc hZjQg ef CbGe ai HdOg GQHY Sfjf fSH GdjgG hGddg GYde s
(3GdfSNI HgG MhGTs
(3bhHdJ HfSNI bhHdJ Ydi NW GdeUfas
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B207 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B257s
Keywords: (3GdMOjK h GdeUWdMs